Cephalosporins determination with a novel microbial biosensor based on permeabilized pseudomonas aeruginosa whole cells - Kumar S.; Kundu S.; Pakshirajan K.; Dasu V.V. (My University, 2025)
A new potentiometric microbial biosensor based on Pseudomonas aeruginosa was developed in this study for detecting the cephalosporin group of antibiotics. Preliminary results with the biosensor indicated that P. aeruginosa cells, when treated with lysozyme, showed more efficiency in detecting cephalosporin C in a wide concentration range of 0.1-11 mM with high sensitivity compared to the normal cells. Optimization of the three important biosensor design parameters permeabilized cell contents, quantities of gelatin, and glutaraldehyde resulted in high performance of the biosensor. The optimized values of the above parameters were cell contents 2.5 mg/cm2, gelatin 8.5 mg/cm2, and 0.25% glutaraldehyde. The assay conditions, namely phosphate buffer pH, ionic strength, and temperature, were optimized for best performance of the biosensor. The specificity test of the biosensor towards detecting different β-lactam antibiotics showed good response only for the cephalosporins. The operational and storage stability in detecting cephalosporin C indicated very good potential of the biosensor in detecting cephalosporins with high accuracy. © 2008 Humana Press.